Deformation mechanisms and plasticity of ultrafine-grained Al under complex stress state revealed by digital image correlation technique - Zhao Yonghao (De Gruyter, 2021)
Conventional engineering stress–strain curve could not accurately describe the local deformability of the tensile necking part because the strain is calculated by assuming that the tensile specimen was deformed uniformly. In this study, we used 3D optical measuring digital image correlation to systematically measure the full strain field and actual flow stress in the necking region of ultrafine-grained (UFG) Al. The post-necking elongation and strain hardening exponent of the UFG Al were measured as 80% and 0.10, slightly smaller than those of the coarse-grained Al (117% and 0.28), suggesting the high plastic deformability of the UFG Al under complex stress state. Microstructural studies revealed the shear and ductile fracture, numerous micro-shear bands, and elongated UFG grains in the UFG Al, which are controlled by cooperative grain boundary sliding and multiple dislocation slips.